Odpowiedzi

2009-12-02T20:39:25+01:00
A)
5x = 4 - 2y
4x + y = 3

5x = 4 - 2y
y = 3 - 4x

5x = 4 - 2(3-4x)
5x = 4 - 6 + 8x
-3x = - 2
x = -2 / 3
y = 3 - 4(-2/3)
y = 3 i 8 / 3
b)
6x - 3y = 9
x + 5y = -9,5

6x - 3y = 9
x = -9,5 - 5y

6(-9,5 - 5y) - 3y = 9
57 - 30y - 3y = 9
-27y = -48
9y = 16
y = 16/9
x = -9,5 - 80 / 9
x = - 331/18
2009-12-02T20:41:45+01:00
5x = 4 - 2y
4x + y = 3 I-4x
5x = 4 - 2y
y=3-4x
5x=4-2(3-4x)
y=3-4x
5x=4-6+8x I-8x
y=3-4x
-3x=-2 I÷-3
y=3-4x
x=2/3
y=3-4*2/3
x=2/3
y=1/3










b)
6x - 3y = 9
x + 5y = -9,5 I-5y
6x - 3y = 9
x=-9,5-5y
6*(-9,5-5y)=9
x=-9,5-5y
-57-30y=9 I+57
x=-9,5-5y
-30y=66 I÷(-30)
x=-9,5-5y
y=2,2
x=-9,5-5*2,2
y=2,2
x=20,5